2011
DOI: 10.1021/jp2062404
|View full text |Cite
|
Sign up to set email alerts
|

Simulating pH Titration of a Single Surfactant in Ionic and Nonionic Surfactant Micelles

Abstract: Calculation of surfactant pK(a)'s in micelles is a challenging task using traditional electrostatic methods due to the lack of structural data and information regarding the effective dielectric constant. Here we test the implicit- and hybrid-solvent-based continuous constant pH molecular dynamics (CpHMD) methods for predicting the pK(a) shift of a lauric acid solubilized in three micelles: dodecyl sulfate (DS), dodecyltrimethylammonium (DTA), and dodecyltriethylene glycol ether (DE3). Both types of simulations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(50 citation statements)
references
References 54 publications
3
47
0
Order By: Relevance
“…At pH 7 a strong peak appears in the RDF between the carboxylate-oxygen and sodium ion near 2.5 Å, suggesting that the counterion is attracted to the carboxylate group upon deprotonation ( Figure 6(d)), consistent with the observation of ionization-induced condensation of counterions around the titratable site made in the CpHMD simulation of micelles. 16 …”
Section: Ph-dependence Of the Conformational States Solvent And Counmentioning
confidence: 99%
See 1 more Smart Citation
“…At pH 7 a strong peak appears in the RDF between the carboxylate-oxygen and sodium ion near 2.5 Å, suggesting that the counterion is attracted to the carboxylate group upon deprotonation ( Figure 6(d)), consistent with the observation of ionization-induced condensation of counterions around the titratable site made in the CpHMD simulation of micelles. 16 …”
Section: Ph-dependence Of the Conformational States Solvent And Counmentioning
confidence: 99%
“…15 This hybrid-solvent scheme, combined with a pH-based replicaexchange protocol, 15 has been shown to offer more realistic pH-dependent conformational sampling and more accurate pK a prediction for proteins 15 as well as surfactant micelles. 16 Most recently, two groups have reported on the development of CpHMD techniques based solely on explicit-solvent models and testing on small model systems. 17,18 In these implementations the GB-based single-site CpHMD method 7 was extended to explicit-solvent simulations by replacing the calculation of solvation forces due to the GB model with deriving forces on real and λ particles from interactions involving explicit water molecules.…”
Section: Introductionmentioning
confidence: 99%
“…17 In comparison to the pK a 's calculated from the GB-based CpHMD simulations, a dramatic difference is seen for the cationic micelle of dodecyl trimethylammonium chloride (DTA, Figure 1, middle). The hybrid-solvent CpHMD resulted in a positive pK a shift of 1.5 (relative to the model value), much closer to the experimental shift of 0.1 compared to the negative shift of −3.0 from the GB-based CpHMD.…”
Section: Introductionmentioning
confidence: 94%
“…The hybrid-solvent CpHMD resulted in a positive pK a shift of 1.5 (relative to the model value), much closer to the experimental shift of 0.1 compared to the negative shift of −3.0 from the GB-based CpHMD. 17 The analysis suggested that the improvement is due to the more accurate representation of the conformational dynamics of the micelle, which is too rigid and compact in the GB solvent, while the remaining error, i.e., overestimation of the pK a shift, is due to the neglect of the effect of explicit ions, which is significant for the DTA micelle but cannot be captured by the Debye-Hückel screening term in the hybrid-solvent CpHMD. 17 Most recently, an all-atom CpHMD method was developed, which uses explicit solvent to drive the dynamics in both conformational and protonation states, thus enabling the effects of ions to be explicitly taken into account.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation